2016
DOI: 10.1175/mwr-d-15-0224.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Sensitivity of Tropical Cyclone Intensification under Upper-Level Trough Forcing

Abstract: This study is part of the efforts undertaken to resolve the ''bad trough/good trough'' issue for tropical cyclone (TC) intensity changes and to improve the prediction of these challenging events. Sensitivity experiments are run at 8-km resolution with vortex bogusing to extend the previous analysis of a real case of TC-trough interaction (Dora in 2007). The initial position and intensity of the TC are modified, leaving the trough unchanged to describe a realistic environment. Simulations are designed to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 75 publications
(73 reference statements)
0
26
0
Order By: Relevance
“…Vollaro (1989, 1990) propose that positive EFC triggers an inward-propagating maximum in y r, which produces a balanced vortex response and thereby is associated with an inward-propagating region of vertical velocity w. This inward-propagating region of positive w would then trigger a secondary eyewall formation, associated with a temporary weakening of the TC but followed by a stronger final intensity due to the convergence of angular momentum associated with the eddies. Leroux et al (2013) found a similar evolution, with trough interaction triggering secondary eyewall formation for TC Dora in the Indian Ocean. In a follow-on study, Leroux et al (2016) found an optimal position of the TC relative to the trough in order for favorable interaction to occur.…”
Section: Introductionmentioning
confidence: 59%
“…Vollaro (1989, 1990) propose that positive EFC triggers an inward-propagating maximum in y r, which produces a balanced vortex response and thereby is associated with an inward-propagating region of vertical velocity w. This inward-propagating region of positive w would then trigger a secondary eyewall formation, associated with a temporary weakening of the TC but followed by a stronger final intensity due to the convergence of angular momentum associated with the eddies. Leroux et al (2013) found a similar evolution, with trough interaction triggering secondary eyewall formation for TC Dora in the Indian Ocean. In a follow-on study, Leroux et al (2016) found an optimal position of the TC relative to the trough in order for favorable interaction to occur.…”
Section: Introductionmentioning
confidence: 59%
“…How RWB affects TC development involves competing physical processes (Leroux et al 2016) and is often obscured by transient features. Studying a large number of cases is thus very demanding and likely undermined by the subjectivity in analyses.…”
Section: Variability Of Rwb Occurrence and Tc Activitymentioning
confidence: 99%
“…Intensification (i.e., positive PER) promotes the slight shrinking of TCs in all basins. Similarly, positive (Northern Hemisphere) REFC, as it promotes vortex intensification when other factors are held constant or favorable (e.g., Molinari andVollaro 1989, 1990;DeMaria et al 1993;Leroux et al 2016, and additional references therein), also promotes a reduction in storm sizes. Positive Z850 (Northern Hemisphere) appears to be related to TC growth in the SHEM and WPAC where TCs often form in monsoon trough environments (equatorial westerlies converging with poleward easterlies).…”
Section: A Selected Variables and Interpretationmentioning
confidence: 99%